2007
DOI: 10.1108/03090560710773381
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal trust between marketing and R&D during new product development projects

Abstract: Purpose -The primary objective of this research is to test a model examining interpersonal trust between marketing managers and R&D managers during new product development projects. Design/methodology/approach -In this study interpersonal trust as a bi-dimensional construct with cognitive and affective components is conceptualised. The authors' integrative structural model specifies Weber's structural/bureaucratic dimensions -formalisation and centralisation to predict three communication dimensions, communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 89 publications
4
101
0
8
Order By: Relevance
“…On the other hand, affect-based trust is grounded in the emotional links between individuals (Lewis and Weigert, 1985). Affectbased trust involves reciprocated interpersonal care and concern for another person (Pennings and Woiceshyn, 1987;Rempel et al, 1985), subjective feelings of security against being exploited, and the comfort and assurance that one's interests are being served by another party (Mittal, 1996;Massey and Kyriazis, 2007).…”
Section: Interpersonal Organizational Trustmentioning
confidence: 99%
“…On the other hand, affect-based trust is grounded in the emotional links between individuals (Lewis and Weigert, 1985). Affectbased trust involves reciprocated interpersonal care and concern for another person (Pennings and Woiceshyn, 1987;Rempel et al, 1985), subjective feelings of security against being exploited, and the comfort and assurance that one's interests are being served by another party (Mittal, 1996;Massey and Kyriazis, 2007).…”
Section: Interpersonal Organizational Trustmentioning
confidence: 99%
“…For instance, several studies hypothesized and concluded that it is communication that affects trust formation (Allert & Chatterjee, 1997;Massey & Kyriazis, 2007;Kottila & Ronni, 2008, Webster & Wong, 2008Thomas et al, 2009). In contrast, several other studies found that trust precedes effective communication and is a critical determinant of trust building (Mellinger.…”
mentioning
confidence: 99%
“…Although previously studied (Hulland et al, 2012;Massey & Kyriazis, 2007), future work could add objective measures, such as new product turnover, market share, and mix participation. Although this research yields no significant differences between hierarchical levels, further work should focus on lower levels, where more conflicts could arise.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%